Adenovirus-Vectored COVID-19 Vaccine–Induced Immune Thrombosis of Carotid Artery: A Case Report. (12th October 2021) - Walter, Uwe; Fuchs, Mario; Grossmann, Annette; Walter, Michael; Thiele, Thomas; Storch, Alexander; Wittstock, Matthias
Abstract : Objectives: Venous thrombosis and thrombocytopenia after vaccination with the adenovirus-vectored COVID-19 vaccine ChAdOx1 nCov-19 (AstraZeneca) have been linked to serum antibodies against platelet factor 4 (PF4)-polyanion complexes. We here report vaccine-induced isolated carotid arterial thrombosis. Methods: Imaging and laboratory findings, treatment decisions, and outcome of this case are presented. Results: Eight days after having received the first dose of ChAdOx1 nCov-19 vaccine, a 31-year-old man was admitted to our stroke unit with acute headache, aphasia, and hemiparesis. D-dimers were slightly elevated, but platelet count and fibrinogen level were normal. MRI-confirmed mainstem occlusion of middle cerebral artery resolved within 1 hour after the start of IV thrombolysis. A wall-adherent, nonoccluding thrombus in the ipsilateral carotid bulb was identified as the source of embolism. Cardiac or paradoxical (venous) embolism was excluded. Screening for the presence of heparin-induced thrombocytopenia–related antibodies was positive, and highly elevated serum IgG antibodies against PF4-polyanion complexes were subsequently proven. Treatment with aspirin and subcutaneous danaparoid, followed by phenprocoumon, led to thrombus shrinkage and dissolution within 19 days and favorable clinical outcome. Discussion: Vaccine history is important in patients not only with venous but also with arterial thromboembolic events. Vaccine-induced immune thrombosis of brain-supplying arteries may well be handled.